Old well sidetracking selection standards: Sulige low-permeability gas field, China - Yingzhong Yuan; Zhilin Qi; Wende Yan; Ji Zhang; Cen Chen (Journal of Petroleum Exploration and Production Technology, 2020)
Abstract The old well sidetracking technology is an effective means to stabilize production and increase recovery in later stage of gas field development. Based on economical and reservoir geologic parameters of Sulige low-permeability gas field in China, method and procedure of old well sidetracking selection standards are established, which can effectively improve the sidetracking effect and adequately develop remaining gas. Comprehensively considering corresponding economic parameters including sidetracking drilling cost, operating cost, management cost, gas production rate and gas price, recoverable reserve standard of sidetracking well is determined first. According to gas recovery, gas-bearing area, porosity and gas saturation, standards of remaining geological reserve, reserve abundance and gas pay thickness of sidetracking well are obtained. According to extension direction and distribution characteristics of the sand body in research area, numerical simulation conceptual model of typical sidetracking horizontal well is established, and then standards of old gas well production rate and gas cumulative production rate for sidetracking are obtained. According to the standards, well Su 36-6-9CH is selected to be sidetracked as a horizontal well and its development effect is good. The method has important value of popularization and application in similar low-permeability gas reservoir.